Functional capacity of elder elderly: comparative study in three regions of Rio Grande do Sul (Revista Latino-Americana de Enfermagem, 2010)
Study conducted with secondary data from cross-sectional population-based studies developed in three regions of the state of Rio Grande do Sul (RS), which aimed to compare the level of dependency for activities of daily living (ADL) of 155 older persons aged 80 years and over. Demographic data and the ADL scale from the 3 studies were used and a multinomial multivariate logistic regression analysis was carried out. The older persons from the urban region of Porto Alegre/RS and from the Northern region of this state presented significantly higher severe dependency than people from the countryside. The results illustrate the heterogeneity of the aging process. Health policies and actions should be planned for the elder elderly in this state.